Safety and efficacy of canine recombinant IL-15 in mammary gland tumors - Kang, Min-Hee; Lee, Jaeil; Kim, Sang-Ki; Koh, Kyeyoung; Kang, Mi-Ae; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
This study investigated the safety and therapeutic potential of recombinant canine interleukin-15 (rcIL-15) as an adjunct to surgical excision in dogs with mammary gland tumors (MGTs). Sixty-one client-owned dogs were initially enrolled, and 55 completed the 12-week study. Dogs were assigned to a test group receiving rcIL-15 with surgery or a control group undergoing surgery alone. RcIL-15 was administered intravenously at 20 μg/kg/day for two 4-day cycles, separated by a 10-day rest period. Clinical monitoring included physiological assessments, blood tests, and owner-reported quality of life (QoL) questionnaires. No significant adverse changes were observed in hematological, biochemical, or physiological parameters. RcIL-15 was well tolerated, with only mild and self-limiting gastrointestinal signs and injection site reactions. Dogs in the rcIL-15 group showed significantly improved QoL, particularly in pain, appetite, and activity. Notably, serum C-reactive protein levels decreased over time in the rcIL-15 group, suggesting reduced systemic inflammation. VEGF levels remained stable in the test group but increased in controls, while IFN-γ concentrations rose significantly following rcIL-15 treatment, indicating immune activation. These findings suggest that rcIL-15 may enhance antitumor immunity and alleviate tumor-related inflammation without compromising safety. The combination of surgery and rcIL-15 improved clinical outcomes compared to surgery alone, supporting its use as a novel immunotherapeutic adjunct for canine MGTs. However, limitations include the short follow-up period and lack of cellular immune profiling. Further studies with longer follow-up and immunological assessment are warranted to confirm these results and explore the broader application of rcIL-15 in veterinary oncology.